(untitled) (Research, Society and Development, 2021)
Objective: To describe the effectiveness of health education actions in the control and prevention of cervical cancer. Methodology: The article used the methodology of integrative literature review with qualitative-descriptive basis, the collection in electronic repositories took place from August 2020 to November 2021, 1,411 articles were found, after analysis and exclusion of those who did not meet the research used a total of 14. Results: Different studies employ heterogeneous means of communication to foster knowledge about cervical cancer, as well as its risks, clinical manifestations, treatment and prevention, such as: phone calls, slide presentation, group discussion, informative lectures, counseling, among others. Conclusion: The actions of health education become a very promising strategy, since it is a low-cost activity that allows the dissemination of information and knowledge to the population in broad aspect, corroborating the increase in demand for those who receive the educational actions for vaccination against HPV and the Pap smear test.